2002
DOI: 10.1614/0890-037x(2002)016[0421:sczmcs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn (Zea mays) Cultivar Sensitivity to Mesotrione*

Abstract: Field studies were conducted in 1999 and 2000 at Simcoe, Ridgetown, and Exeter, Ontario, to evaluate the tolerance of nine sweet corn cultivars to mesotrione, applied preemergence (PRE) at 140 and 280 g ai/ha and postemergence (POST) at 100 and 200 g ai/ha. Urea ammonium nitrate fertilizer (28%) at 2.5% (v/v) and crop oil concentrate at 1% (v/v) were added to POST applications of mesotrione only. All cultivars were tolerant to mesotrione applied PRE. There was no injury, or reductions in plant height or yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 13 publications
6
51
0
2
Order By: Relevance
“…(1 (O'Sullivan et al 2002;Armel et al 2003) and 58% transient leaf necrosis immediately after treatment with fluthiacet-methyl (Fausey et al 2001). Sellers et al (2009) reported that dogfennel [Eupatorium capillifolium (Lam.)…”
Section: Kochiamentioning
confidence: 99%
“…(1 (O'Sullivan et al 2002;Armel et al 2003) and 58% transient leaf necrosis immediately after treatment with fluthiacet-methyl (Fausey et al 2001). Sellers et al (2009) reported that dogfennel [Eupatorium capillifolium (Lam.)…”
Section: Kochiamentioning
confidence: 99%
“…Os sintomas se desenvolvem mais rapidamente na presença de luz (Pallet et al, 1998;Wichert et al, 1999;Johnson & Young, 2002) O mesotrione causa em algumas variedades ou híbrido de milho sintomas de fitointoxicação, porém isso não resulta em perdas na produtividade de grãos (Furtado, 2004;Masiunas et al, 2004). O milho é tolerante ao mesotrione, provavelmente, devido à capacidade de desativação do princípio ativo e à translocação para compartimentos celulares -vacúolo e meio extracelular (Mitchell et al, 2001;Johnson & Young, 2002;O´Sullivan et al, 2002). A capacidade de realizar a desintoxicação de herbicida é desencadeada pelo aparato bioquímico celular (Kreuz et al, 1996).…”
Section: Introductionunclassified
“…However, other herbicides such as bentazon [11], isoxaflutole [17], mesotrione [13], nicosulfuron [14,23], nicosulfuron plus rimsulfuron [24,25], primisulfuron [16], prosulfuron [12] or thifensulfuron-methyl [18] have been shown to cause significant injury in some sweet maize hybrids.…”
Section: Crop Injurymentioning
confidence: 99%
“…Sensitivity of sweet maize to herbicides is dependent on the application dose, hybrid, and environmental conditions. Sweet maize hybrid sensitivity has been documented for foramsulfuron [10], bentazon [11], prosulfuron [12], mesotrione [13], nicosulfuron [14,15], primisulfuron [16], isoxaflutole [17], and thifensulfuron-methyl [18].…”
Section: Introductionmentioning
confidence: 99%